Development of Digital Literacy in the Community Through Student Mentoring: A Study on the Implementation of QRIS in Rajang Village, Pinrang Regency - Tahir G, Muhammad; Herniah, Herniah (Universitas Pejuang Republik Indonesia, 2025)
The development of digital technology has brought significant changes in various aspects of life, including in the economic transaction system. However, in many rural areas, the low level of digital literacy is still a major challenge in the application of new technologies. This research aims to analyze the development of digital literacy among the community through student assistance in the implementation of QRIS (Quick Response Code Indonesian Standard) in Rajang Village, Pinrang Regency. This research uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation during the Community Service Program (KKN) activities. Students who are members of the KKN program conduct socialization, training, and assistance to the community, especially UMKM players, to adopt a QRIS-based digital payment system. The results showed that student mentoring contributed significantly to the improvement of community digital literacy. People who initially did not understand the QRIS concept and were reluctant to switch from cash transactions, gradually showed an increase in knowledge and confidence in using the digital system. In addition, UMKM players in Rajang Village began to feel the benefits of transaction efficiency and increased their business competitiveness. The active role of students as technology facilitators is a key factor in the success of this program. In conclusion, student involvement in community service programs can be an effective strategy in encouraging digital transformation in villages. Continuous collaboration between universities, village governments, and digital service providers is needed to expand the positive impact of digital literacy development.